Health Literacy Promotion and Its Institutional Arrangements: Rethinking collaborative health promotion in Thailand - Watcharabon Buddharaksa; Jonathan S. Davies; Phudit Tejativaddhana (ACHSM, 2021)
This research explores institutional arrangements that govern health literacy promotion policies in Thailand since 2014. This study sets the main questions as what are the main institutional arrangements that governed health literacy promotion policies in Thailand since 2014 and can these arrangements be viewed as collaborative health governance? This paper argues that the military coup in 2014 transformed institutional-governing arrangements on health system management and health promotion greatly as many legal-political institutions and various social-political agencies were involved and brought together to promote health and health literacy. A so-called principle of 'collaborative governance' has been employed and implemented to promote health in Thailand recently, however, this study argues that the institutional constraints under authoritarian regime offer a 'fictitious-collaborative health governance' instead. Furthermore, deliberative processes on health literacy promotion regulated by many legal - institutional constraints had characteristics of 'pseudo-deliberation'. This work is qualitative research, and it analyzes and explains research results by looking through theoretical concepts of institutionalism and collaborative governance. This study argues that to reach the goal of health literate community and society, Thai health agencies and authorities should re-approach health and health literacy promotion from the bottom-up perspective. Also, overcoming fictitious collaborative health promotion and pseudo-deliberation are necessary. To do that, we need a long-term project of building up a 'critical health regime' based on critical education and anti-authoritarianism as major principles. (*The paper was presented at The Hong Kong Polytechnic University's College of Professional and Continuing Education (CPCE) Conference "Post-pandemic health and long-term care: A new paradigm". September 2021)